An Analysis of the Students' Difficulties in Writing Undergraduate Thesis at English Education Study Program of Muhammadiyah University of Bengkulu - Dwi Monica Lestari (UNIVERSITAS MUHAMMADIYAH METRO (MUHAMMADIYAH UNIVERSITY OF METRO), 2020)
The objectives of this research are: 1) To find out the undergraduate students Difficulties In Writing Thesis at The English Study Program of Muhammadiyah University Bengkulu (UMB) in Academic Year 2018-2019, and 2) To find out the most difficult variable they faced in writing theses. The design of this research is descriptive quantitative research. 74 students of the Seventh Semester Students of English Education Study Program of Muhammadiyah University of Bengkulu in the Academic Year of 2018-2019 took part in this study. The instruments were questionnaires and interview. The data were collected by assigning the students to fill out the questionnaires and being interviewed afterward. The data were analyzed by checking the students answer in the questionnaire, classifying the students answers, calculating the students scores of difficulties in writing a thesis, describing the data and concluding the results. The results showed the students' difficulties in writing a thesis; a) Orderly, the students' difficulties in writing a thesis are: related to difficulties of students' English proficiencies; related to difficulties of students' time management; related to difficulties of students' research methodology; related to difficulties of students' attitude; related to difficulties of students' research topic; and the least related to difficulties of a co-advisor relationship, students' plagiarism, students' personalities, the big number of supervised students and advisor workload; and difficulties of students motivation. b) The most difficulties in writing thesis are related to their English proficiency which are still low and limited. Both have become the first cause that they cannot develop their writing thesis well. The implication of this study ; 1) the students should minimize their difficulties and find the solution in the way of a) Improve their English, or at least have adequate English before writing a thesis. b) Should manage their time wisely in doing their thesis. c) Read more relevant sources that can support their research. d) Give more attention to avoid plagiarism. 2) Further researchers are suggested to do similar research and add more data with adding research instruments, such as interview guides.